"Bad Enough to Cook for Two, Worse for One" – Mixed Method Evaluation of Eating Behavior among Community Dwelling Older Adults. Issue 3 (1st October 2020) - Knippen, Kerri Lynn; Lee, HeeSoon; Ford, Tasha; Welch, Philip
Abstract: Food insecurity, life events, and emotional eating can influence dietary patterns. However, their interaction among older adults requires further investigation. This mixed-method, interdisciplinary project included 7 focus groups and a cross-sectional survey ( n = 55) to evaluate these factors among older adults (60–102 years of age) living in rural Ohio communities. Qualitative data highlighted critical life events, emotions and personal relationships, food insecurity, and learning how to do more with less, and resilience in dietary patterns. The majority of the participants were overweight or obese. Food insecurity, frequency of congregate meals, and age were associated with emotional eating. Attributes of diet quality correlated with emotional eating and food insecurity. Future work should address the unique needs of older adults by expanding food assistance programs, while including the older adult's perspectives with regard to life experiences, the value of social support, personal relationships, and honoring food preferences, particularly nutrient-dense foods.